OLFM4, LY6D and S100A7 as potent markers for distant metastasis in estrogen receptor‐positive breast carcinoma. Issue 10 (27th September 2018) - Mayama, Akifumi; Takagi, Kiyoshi; Suzuki, Hiroyoshi; Sato, Ai; Onodera, Yoshiaki; Miki, Yasuhiro; Sakurai, Minako; Watanabe, Takanori; Sakamoto, Kazuhiro; Yoshida, Ryuichi; Ishida, Takanori; Sasano, Hironobu; et al.
Abstract : Metastatic breast cancer is a highly lethal disease, and it is very important to evaluate the biomarkers associated with distant metastasis. However, molecular features of distant metastasis remain largely unknown in breast cancer. Estrogens play an important role in the progression of breast cancer and the majority of stage IV breast carcinomas express estrogen receptor (ER). Therefore, in this study, we examined molecular markers associated with distant metastasis in ER‐positive breast carcinoma by microarray and immunohistochemistry. When we examined the gene expression profile of ER‐positive stage IV breast carcinoma tissues (n = 7) comparing ER‐positive stage I‐III cases (n = 11) by microarray analysis, we newly identified OLFM4, LY6D and S100A7, which were closely associated with the distant metastasis. Subsequently, we performed immunohistochemistry for OLFM4, LY6D and S100A7 in 168 ER‐positive breast carcinomas. OLFM4, LY6D and S100A7 immunoreactivities were significantly associated with stage, pathological T factor, distant metastasis and Ki67 status in the ER‐positive breast carcinomas. Moreover, these immunoreactivities were significantly associated with a worse prognostic factor for distant metastasis‐free and breast cancer‐specific survival in ER‐positive stage I‐III breast cancer patients. However, when we performed immunohistochemistry for OLFM4, LY6D and S100A7 in 40 ER‐negative breast carcinomas, these immunoreactivities were not generally associated with the clinicopathological factors examined, including distant metastasis and prognosis of patients, in this study. These results suggest that OLFM4, LY6D and S100A7 immunoreactivity are associated with an aggressive phenotype of ER‐positive breast carcinoma, and these are potent markers for distant metastasis of ER‐positive breast cancer patients. Abstract : This is the first report that demonstrates the gene expression profile of estrogen receptor (ER)‐positive stage IV breast carcinoma, and we newly identified that OLFM4, LY6D and S100A7 were associated with the distant metastasis. A subsequent immunohistochemical analysis revealed that OLFM4, LY6D and S100A7 immunoreactivity were significantly associated with an aggressive phenotype of ER‐positive breast carcinoma including distant metastasis and a worse prognostic factor of the patients. Our present results suggest that OLFM4, LY6D and S100A7 are potent markers for distant metastasis, and could become important therapeutic targets in ER‐positive breast cancer patients.